2014
DOI: 10.5312/wjo.v5.i3.188
|View full text |Cite
|
Sign up to set email alerts
|

New oral pharmacotherapeutic agents for venous thromboprophylaxis after total hip arthroplasty

Abstract: Patients undergoing total hip arthroplasty (THA) are at high risk for developing venous thromboembolism and, therefore, require short term prophylaxis with antithrombotic agents. Recently, target specific oral anticoagulants (TSOA) including the direct thrombin inhibitor, dabigatran, and the factor Ⅹa inhibitors rivaroxaban, apixaban, and edoxaban have been approved for THA thrombopropylaxis in various countries. The TSOAs provide a rapid acting, oral alternative to parenteral agents including low-molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“… 7 , 32 The preference of these agents, nonetheless, has declined due to major bleeding risk and adherence issues related to the inconvenient route of administration; several studies have thus far evaluated the thromboprophylactic effects of oral anticoagulants, both in cancer and non-cancer patients, as an alternative option to replace parenteral agents. 13–15 , 33 , 34 Two RCTs with the follow-up of 180 days demonstrated the efficacy of apixaban and rivaroxaban, respectively, along with an improved safety profile in terms of lower major bleeding risk in cancer patients as compared to placebo. 13 , 14 In consistent with these results, our study confirmed that NOACs significantly reduced thrombosis risks in terms of VTE as a whole and more specifically in DVT among cancer patients; bleeding risk was also assessed lower in those receiving NOACs relative to non-users.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 32 The preference of these agents, nonetheless, has declined due to major bleeding risk and adherence issues related to the inconvenient route of administration; several studies have thus far evaluated the thromboprophylactic effects of oral anticoagulants, both in cancer and non-cancer patients, as an alternative option to replace parenteral agents. 13–15 , 33 , 34 Two RCTs with the follow-up of 180 days demonstrated the efficacy of apixaban and rivaroxaban, respectively, along with an improved safety profile in terms of lower major bleeding risk in cancer patients as compared to placebo. 13 , 14 In consistent with these results, our study confirmed that NOACs significantly reduced thrombosis risks in terms of VTE as a whole and more specifically in DVT among cancer patients; bleeding risk was also assessed lower in those receiving NOACs relative to non-users.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are no methods for monitoring their anticoagulant effect. However, because the newer anticoagulants have a shorter half-life than warfarin or fondaparinux, antidotes may be less essential than with previous agents 140 and there have been recommendations in treatment guidelines as to how to effect reversal of these new agents if necessary 111,147-…”
Section: Thromboprophylaxis: the Optionsmentioning
confidence: 99%
“…This regimen of enoxaparin sodium was prescribed by the local protocol. In the postoperative period, the pharmacoprophylaxis of all patients was combined with elastic compression of the lower extremities and early activation [2,4,5]. Fibrinolysis inhibitors for the prevention of hemorrhagic complications were not used.…”
Section: Methodsmentioning
confidence: 99%
“…The use of some modern oral anticoagulants for VTEC prevention in this category of patients becomes more popular [5]. Nevertheless, the problem of venous thromboembolism in total HR is still relevant [5].…”
Section: Introductionmentioning
confidence: 99%